Diagnosis of Epstein-Barr virus infection in clinical serum samples by an SPR biosensor assay - Riedel, Tomáš; Rodriguez-Emmenegger, Cesar; de los Santos Pereira, Andres; Bědajánková, Anna; Jinoch, Pavel; Boltovets, Praskovia M; Brynda, Eduard (Biosensors & bioelectronics, 2014)
Label-free affinity biosensors offer a promising platform for the development of a new generation of medical diagnostic technologies. Nevertheless, when such sensors are used in complex biological media, adsorption of non-targeted medium components prevents the specific detection of the analyte. In this work, we introduce for the first time a biosensor assay based on surface plasmon resonance (SPR) capable of diagnosing different stages of Epstein-Barr virus (EBV) infections in clinical serum samples. This was achieved by simultaneous detection of the antibodies against three different antigens present in the virus. To prevent the interference of the fouling from serum during the measurement, the SPR chips were coated by an antifouling layer of a polymer brush of poly[oligo(ethylene glycol) methacrylate] grown by surface-initiated atom transfer radical polymerization. The bioreceptors were then attached via hybridization of complementary oligonucleotides. This allowed the sensor surface to be regenerated after measurement by disrupting the complementary pairs above the oligonucleotides' melting temperature and attaching new bioreceptors. In this way, the same sensing surface could be used repeatedly. The procedure used in this work will serve as a prototype strategy for the development of label-free affinity biosensors for diagnostics in blood serum or plasma samples. This is the first example of detection of marker of a disease in clinical serum samples by an optical affinity biosensor.
Keywords: Equipment Design; Immunoassay; Surface Plasmon Resonance; povrchová plasmonová rezonance; analýza selhání vybavení; Reproducibility of Results; lidé; Sensitivity and Specificity; senzitivita a specificita; Equipment Failure Analysis; Biosensing Techniques; protilátky virové; reprodukovatelnost výsledků; infekce virem Epsteina-Barrové; imunoanalýza; biosenzitivní techniky; Epstein-Barr Virus Infections; Antibodies, Viral; design vybavení; Humans